Intestine Bacterial Community Composition of Shrimp Varies Under Low- and High-Salinity Culture Conditions - Hou, Dongwei; Zhou, Renjun; Zeng, Shenzheng; Wei, Dongdong; Deng, Xisha; Xing, Chengguang; Yu, Lingfei; Deng, Zhixuan; Wang, Hao; Weng, Shaoping; He, Jianguo; Huang, Zhijian (Frontiers in Microbiology, 2020)
Intestine microbiota is tightly associated with host health status. Increasing studies have focused on assessing how host intestine microbiota is affected by biotic factors, but ignored abiotic factors. Here, we aimed to understand the effects of salinity on shrimp intestine microbiota, by comparing the differences of intestine bacterial signatures of shrimp under low-salinity (LS) and high-salinity (HS) culture conditions. Our results found that intestine core bacterial taxa of shrimp under LS and HS culture conditions were different, and that under HS contained more opportunistic pathogen species. Notably, compared with LS culture condition, opportunistic pathogens (e.g., Vibrio species) were enriched in shrimp intestine under HS. Network analysis revealed that shrimp under HS culture condition exhibited less connected and lower competitive of intestine bacterial interspecies interactions compared with LS. In addition, under HS culture condition, several opportunistic pathogens were identified as keystone species of intestine bacterial network in shrimp. Furthermore, the ecological drift process played a more important role in the intestine bacterial assembly of shrimp under HS culture condition than that under LS. These above traits regarding the intestine microbiota of shrimp under HS culture condition might lead to host at a higher risk of disease. Collectively, this work aids our understanding of the effects of salinity on shrimp intestine microbiota, and help for shrimp culture.